2021
DOI: 10.3390/ma14185161
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thermodynamic Conditions for the Formation of p-Type β-Ga2O3 with Cu Doping

Abstract: As a promising third-generation semiconductor, β-Ga2O3 is facing bottleneck for its p-type doping. We investigated the electronic structures and the stability of various Cu doped structures of β-Ga2O3. We found that Cu atoms substituting Ga atoms result in p-type conductivity. We derived the temperature and absolute oxygen partial pressure dependent formation energies of various doped structures based on first principles calculation with dipole correction. Then, the critical thermodynamic condition for forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Previous studies have reported that Cu can introduce deep acceptor states near the valence band maximum of CuInSe 2 , as depicted in Figure 4. Density‐functional theory calculations have predicted two Cu‐related deep acceptor states, [ 59,60 ] which have also been observed through PL [ 61,62 ] and absorption measurements. [ 63 ] The defect transitions were found between 2.1 and 2.6 eV, which could be the defect close to the valence band of CuInSe 2 .…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have reported that Cu can introduce deep acceptor states near the valence band maximum of CuInSe 2 , as depicted in Figure 4. Density‐functional theory calculations have predicted two Cu‐related deep acceptor states, [ 59,60 ] which have also been observed through PL [ 61,62 ] and absorption measurements. [ 63 ] The defect transitions were found between 2.1 and 2.6 eV, which could be the defect close to the valence band of CuInSe 2 .…”
Section: Resultsmentioning
confidence: 97%
“…However, achieving improved p-type conductivity in β-Ga 2 O 3 has been a persistent challenge. Thus, further research on appropriate acceptor doping is necessary [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…p型. 2023年, Wang等 [11] 利用射频磁控溅射法在 不同沉积温度下, 在蓝宝石衬底上制备了Zn掺杂 b-Ga 2 O 3 薄膜, 研究发现n掺杂b-Ga 2 O 3 薄膜为 p型, 但与未掺杂b-Ga 2 O 3 膜相比, Zn掺杂的b-Ga 2 O 3 膜的载流子浓度和迁移率都较低. 2021年, Zhang等 [12] 基于第一性原理和偶极子修正的理论 计算得出, Cu掺杂b-Ga 卡片JCPDS 43-1012对比后 [13] , 而形成较高的光电流 [14] .…”
unclassified